The Role of Jumiang Beach Halal Tourism in Increasing Income of the Local Communities - Siti Masriyah; Rudi Hermawan (Cahaya Abadi Publisher, 2023)
This study discusses halal tourism as an instrument of Indonesian public diplomacy in order to increase tourist visits and improve the community's economy, where the large potential for halal tourism is expected to have an important role in the regional economy, especially for the people around Jumiang Beach, Pademawu District, Pamekasan Regency. This research used qualitative research to obtain a greater understanding of the phenomenon. The data were data collected from the field directly collected using interview scripts. The results of this study indicate that the economy of the community around Jumiang Beach has increased with the existence of Jumiang Beach. However, it has a decreased trend for tourist due to Covid-19 pandemic.